Description of the adult of the thread-legged assassin bug Eugubinus araneus (Hemiptera: Reduviidae) from India, with comments on other congeneric species - Ghate, Hemant V.; Boyane, Swapnil S.; Webb, Michael D. (Zootaxa, 2021)
The thread-legged assassin bug Eugubinus araneus Distant, 1903 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini) was described from India on the basis of two nymphs. This paper provides the first description of the adult with illustrations of both the adult and the nymph. A checklist of and a key to species of Eugubinus Distant, 1903, and images of the type material of six additional species of the genus, i.e., E. intrudans Distant, 1915, E. reticolus Distant, 1915, E. canalanus (Distant,1914), E. annulatus (Villiers, 1948), E. forsteri Wygodzinsky, 1953 and E. papuensis Wygodzinsky, 1966, are provided.